European integration and the communist dilemma communist party responses to Europe in Greece, Cyprus, and Italy - Charalambous, Giorgos (Routledge, 2016)
European Integration and the Communist Dilemma assesses the response of communist parties to European integration using three contrasting and comparatively significant case studies from Greece, Cyprus and Italy. These parties, in common with other radical parties in Europe.